Mutant Cx30-A88V mice exhibit hydrocephaly and sex-dependent behavioral abnormalities, implicating a functional role for Cx30 in the brain - Nicole M. Novielli-Kuntz; Eric R. Press; Kevin Barr; Marco A. M. Prado; Dale W. Laird (The Company of Biologists, 2021)
Connexin 30 (Cx30; also known as Gjb6 when referring to the mouse gene) is expressed in ependymal cells of the brain ventricles, in leptomeningeal cells and in astrocytes rich in connexin 43 (Cx43), leading us to question whether patients harboring GJB6 mutations exhibit any brain anomalies. Here, we used mice harboring the human disease-associated A88V Cx30 mutation to address this gap in knowledge. Brain Cx30 levels were lower in male and female Cx30A88V/A88V mice compared with Cx30A88V/+ and Cx30+/+ mice, whereas Cx43 levels were lower only in female Cx30 mutant mice. Characterization of brain morphology revealed a disrupted ependymal cell layer, significant hydrocephalus and enlarged ventricles in 3- to 6-month-old adult male and female Cx30A88V/A88V mice compared with Cx30A88V/+ or Cx30+/+ sex-matched littermate mice. To determine the functional significance of these molecular and morphological changes, we investigated a number of behavioral activities in these mice. Interestingly, only female Cx30A88V/A88V mice exhibited abnormal behavior compared with all other groups. Cx30A88V/A88V female mice demonstrated increased locomotor and exploratory activity in both the open field and the elevated plus maze. They also exhibited dramatically reduced ability to learn the location of the escape platform during Morris water maze training, although they were able to swim as well as other genotypes. Our findings suggest that the homozygous A88V mutation in Cx30 causes major morphological changes in the brain of aging mice, possibly attributable to an abnormal ependymal cell layer. Remarkably, these changes had a more pronounced consequence for cognitive function in female mice, which is likely to be linked to the dysregulation of both Cx30 and Cx43 levels in the brain.